Microsurgical Neurovascular Anatomy of the Brain: The Posterior Circulation (Part II) - Giotta Lucifero, Alice; Baldoncini, Matias; Bruno, Nunzio; Tartaglia, Nicola; Ambrosi, Antonio; Marseglia, Gian Luigi; Galzio, Renato; Campero, Alvaro; Hernesniemi, Juha; Luzzi, Sabino (Acta Biomedica Atenei Parmensis, 2021)
Introduction Vascular complications of posterior fossa surgery are often deadly although widely preventable through in-depth knowledge of the microsurgical neurovascular anatomy of the infratentorial region and careful surgical planning.  The target of this study is to provide a synoptic overview of the normal anatomy and anatomic variants of the infratentorial neurovascular system, critical to safely operate tumors and neurovascular pathologies of the posterior fossa.MethodsTwo fresh-frozen and five formalin-fixed cadaveric heads were used. Cervical arteries and internal jugular veins were injected with red and blue latex, respectively. The heads were dissected under a surgical microscope, with magnifications ranging between 3× to 40×, focusing on the infratentorial region. The infratentorial arteries, their collaterals and perforating branches, the brainstem and cerebellar veins, the tentorial venous sinuses, and the relative vascular territories were summarized according to a synoptic approach.   ResultsThe vertebral artery, basilar artery (BA), and posterior cerebral artery (PCA) are the main sources of the arterial supply of the brainstem and cerebellum through the posterior inferior cerebellar artery (PICA), the anterior inferior cerebellar artery (AICA), the superior cerebellar artery (SCA), and the perforating arteries. The perforating arteries of the vertebrobasilar system derive from the PICA, BA, AICA, SCA, and PCA, and provide for a key contribution to the vascularization of the midbrain, pons, medulla oblongata, fourth ventricle, cerebellar and cerebral peduncles, thalamus, hypothalamus, subthalamus, posterior part of the internal capsule, and optic tract. The distal segments and branches of the PCA also add a significant arterial supply to the temporal, occipital, and parietal lobes. The venous outflow of the posterior fossa is a prerogative of the internal jugular veins via the tentorial venous sinuses.ConclusionA perfect mastery of the arterial, venous, and cisternal anatomy of the infratentorial region is vital for the planning and execution of the whole range of posterior fossa approaches.